2013
DOI: 10.1097/hjh.0b013e32835e2286
|View full text |Cite
|
Sign up to set email alerts
|

Resistant hypertension? Assessment of adherence by toxicological urine analysis

Abstract: Low adherence was the most common cause of poor blood pressure control in patients with apparent resistant hypertension, being twice as frequent as secondary causes of hypertension. Incomplete adherence was far more common than complete nonadherence; thus, assessment of adherence in patients on multiple drug regime is only reliable when all drugs are included in assessment. Assessing adherence by toxicological urine screening is a useful tool in detecting low adherence, especially in the setting of multidrug r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
285
4
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 429 publications
(317 citation statements)
references
References 43 publications
14
285
4
14
Order By: Relevance
“…In all of these studies carried out in TRH or hypertensive patients with insufficient BP control, LC‐MS/MS was used to measure the drug levels, allowing a comparison of adherence rates. The definition of partial nonadherence, however, varies widely from “at least one or more substances missing” to “fewer than prescribed” or is not described in detail at all 14, 15, 16, 17. In our study, we used only 1 antihypertensive substances missing for the definition of partial adherence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In all of these studies carried out in TRH or hypertensive patients with insufficient BP control, LC‐MS/MS was used to measure the drug levels, allowing a comparison of adherence rates. The definition of partial nonadherence, however, varies widely from “at least one or more substances missing” to “fewer than prescribed” or is not described in detail at all 14, 15, 16, 17. In our study, we used only 1 antihypertensive substances missing for the definition of partial adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Electronic methods of adherence monitoring (ie, computerized records of pharmacy prescription or electronic monitoring of pill box opening) may be considered reliable alternatives, but it remains subject to the patient's behavior whether the removed pills are indeed ingested 1, 12, 13. Recently, toxicological urine analysis of the compounds or their metabolites has gained increasing interest 14, 15, 16, 17. These biochemical analyses represent spot assessments of adherence but are subject to the “white coat adherence” effect 18, 19.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Recent studies from our group and others have reported a high prevalence of non-adherence to antihypertensive medications among patients with a-TRH (50-60%) using the highly sensitive technique of therapeutic drug monitoring. [2][3][4][5] Despite the enormous burden of non-adherence to the health care system, practical and reliable methods of adherence detection are not well developed. Adherence can be monitored by several methods such as patient self-report, detailed questionnaire, pill counts, prescription fill rate, or electronic pillboxes.…”
Section: Introductionmentioning
confidence: 99%
“…A secondary form of hypertension is often present in treatment-resistant hypertension. Therefore, in the case of insufficient response to treatment with medication, office or white coat hypertension (pseudoresistance) [8,9], unreliable intake of medication [10,11], suboptimal or false medication combination, and secondary types of hypertension must be ruled out as the cause of "treatment-resistant" hypertension.…”
Section: Clinical Practicementioning
confidence: 99%